Characteristics of steroid hormones in systemic lupus erythematosus revealed by GC/MS-based metabolic profiling - Wu, Dehong; Ye, Lingxia; Zhang, Xiafeng; Yin, Mengdi; Guo, Yixuan; Zhou, Jia (Frontiers in Endocrinology, 2023)
Background Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with a remarkable predominance in female, suggesting that steroid hormones may be involved in the pathogenesis. However, steroid signature of SLE patients has not been fully explored. Methods A metabolic profiling analysis based on gas chromatography/mass spectrometry (GC/MS) with high sensitivity and reproducibility was employed to comprehensively reveal SLE-specific steroid alterations. Results More than 70 kinds of steroids in urine were detected by gas chromatography/mass spectrometry (GC/MS) to reveal SLE-specific steroid alterations. Principle component analysis demonstrated that the steroid profile was obviously distinguished between patients with SLE and controls. A lower level of total androgens was observed in patients, and nine androgens [dehydroepiandrosterone (DHEA), testosterone, Etio, androsterone, βαβ-Diol, Epi-An, Epi-DHT, 16α-OH-DHEA, and A-Diol] underwent significant decrease. Moreover, patients with SLE exhibited a slightly higher level of total estrogens than controls, and three estrogens (17-Epi-E3, 17α-E2, and E3) were remarkably increased. Furthermore, we identified the elevation of two sterols (Lan and Chol), and the reduction of one corticoid (11-DeoxyF) and two progestins (5α-DHP and 11β-OH-Prog) in patients. Discussion In this study, metabolic signature of urinary steroids associated with SLE was comprehensively defined by GC/MS for the first time, and steroid metabolism disorders were found in patients with SLE, especially the conversion of androgens to estrogens. Our findings will provide new insights for a deeper understanding of the mechanism of steroid hormones in the pathogenesis of SLE and will help to unravel the reason of sexual disparity in SLE.